THE ROLE OF SELF CHECK-IN FACILITIES AND SERVICE QUALITY ON PASSENGER SATISFACTION AT THE TERMINAL DOMESTIC INTERNATIONAL AIRPORT I GUSTI NGURAH RAI - Irma Binarti; Subandi Subandi (Universitas Budi Luhur, 2023)
I Gusti Ngurah Rai International Airport is an airport managed by PT Angkasa Pura I (PERSERO) on the island of Bali. As a province that is known globally as a tourism destination, this makes I Gusti Ngurah Rai Airport one of the busiest airports in Indonesia and one of the entry gates for tourists to Bali Island. The research objective in this thesis is to see the Effect of Facilities (X1) and Service Quality (X2) on Passenger Satisfaction (Y) at Domestic Terminal I Gusti Ngurah Rai Airport in 2022. To see this problem, the authors use multiple linear regression, coefficient of understanding. multiple, coefficient of determination, and hypothesis testing.